The GCF of 6x and 18x^2 is 6x. By factoring out the GCF, we get:
6x(1 + 3x)
How would you rewrite the expression 6x+18x^2 by factoring out the GCF?(1 point)
5 answers
Solve for x. 7(4x−15)=63 (1 point)
To solve for x, we need to simplify the equation first. Using the distributive property on the left side of the equation:
7(4x - 15) = 28x - 105
Now, our equation becomes:
28x - 105 = 63
Adding 105 to both sides:
28x = 168
Dividing both sides by 28:
x = 6
Therefore, the solution to the equation 7(4x - 15) = 63 is x = 6.
7(4x - 15) = 28x - 105
Now, our equation becomes:
28x - 105 = 63
Adding 105 to both sides:
28x = 168
Dividing both sides by 28:
x = 6
Therefore, the solution to the equation 7(4x - 15) = 63 is x = 6.
Solve for x : −2(3x−15)−25=35 .(1 point)
To solve for x, we need to simplify the equation first by using the distributive property.
Starting with the given equation:
-2(3x - 15) - 25 = 35
First, distribute the -2 on the left side:
-6x + 30 - 25 = 35
Combine like terms:
-6x + 5 = 35
Subtract 5 from both sides:
-6x = 30
Finally, divide by -6:
x = -5
Therefore, the solution to the equation -2(3x - 15) - 25 = 35 is x = -5.
Starting with the given equation:
-2(3x - 15) - 25 = 35
First, distribute the -2 on the left side:
-6x + 30 - 25 = 35
Combine like terms:
-6x + 5 = 35
Subtract 5 from both sides:
-6x = 30
Finally, divide by -6:
x = -5
Therefore, the solution to the equation -2(3x - 15) - 25 = 35 is x = -5.